Detection of Vibrio parahaemolyticus by polymerase chain reaction (PCR) technique - Kadhim, Hadaf Mahdi (Al-Qadisiyah Journal of Pure Science, 2017)
Vibrio parahaemolyticus causes gastroenteritis in humans, this bacterium lives in coastal water during the summer, repetitive extragenic palindromic PCR (REP-PCR), one of the fingerprinting technique that used to analyse the isolates of V. parahaemolyticus tested in the current study, the majority of clinical isolates produced a band at 1000 bp amplicon. The DNA from this band was cloned and sequenced and found to code for a peptide chain release factor 1. The specific PCR amplification results showed that all 100% of the all V. parahaemolyticus strains tested were positive for 400 bp products. None of the other Vibrio species and non-Vibrio produced this amplicon. A PCR method amplifying a 400 bp fragment of the V. parahaemolyticus peptide chain release factor 1 could be useful in the specific and rapid detection of the species.